International implications of the Asian financial crisis a discussion on international financial contagion and new financial architecture - Numanoğlu, Nilüfer (My University, 2000)
ÖZET Uluslararası finansal piyasalar, 1997-98 yıllarında yeni küreselleşme çağındaki en büyük krize sahne oldu. Thailand bahtının devalue edilmesinin ardından gelişen olaylar Avrupa ve Amerikalı yatırımcıların büyük zararlara uğramalarına neden oldu. Asya krizini farklı kılan özellik, krizin ortaya çıkmasından sonra meydana gelen bulaşma etkisinin boyutu olmuştur. Kriz önce Asya'dan Rusya'ya, daha sonra da Rusya'dan Latin Amerika ülkeleri ve Amerika'ya bulaşmıştır. 1997-98 krizlerinden alınması gereken en önemli ders, uluslararası finansal sistemin güçlendirilmek üzere yeniden yapılandırılması gerektiğidir. Bu tez çalışmasında, öncelikle Asya krizinin sebeplerini, uluslararası finansal bulaşma yı ve gelecekte bu tür krizlerden korunma amacıyla finansal yapıyı güçlendirmeye yönelik atılması gereken adımları tartışmak amaçlanmıştır.

In 1997-98, the global financial world has experienced the deepest financial crisis in the new era of globalization. Devaluation of the Thai baht seems to have triggered a chain of events which have led to massive losses on the side of the European and American investors. What has made the Asian crisis different is the severity of the contagious effects that followed the eruption of the crisis. The crisis spread from Asia to Russia and then from Russia to Latin America and the United States. The most crucial lesson to be drawn from the financial crises of 1997-98 is that the international financial system needs to be reformed. In this dissertation, it is attempted to address the causes of the Asian financial crisis, explain international financial contagion, and illustrate the necessary steps that need to be taken in order to reform the international financial system so that the global economic world may be able to withstand the adverse effects of possible future crises.
Keywords: Ekonomi; FİNANS; Finansman ekonomisi